Request for inspection: case study at female dorm 2 / Amir Izzuddin Arifin - Arifin, Amir Izzuddin (Universiti Teknologi MARA, Perak, 2015)
This report tells about ways to inspection and who is involved. Every inspection should be conducted according to a predetermined specification. Site supervisor and consultant to do the work of inspection based on the detail drawing that has been approved by the architect and engineer. In this report there are also those who are responsible and must find a solution in the event of defects in the assembly building element. Every inspection carried out necessary forms called RFI (Form J). The function of this form is to make the inspection carried out by the consultant with the main-contractor remedy approve, approved by remedial work or repair and inspect again for each work structure and architect work done by sub-contractor. This form is also used by a sub-contractor to make a claim to the main-contractor. In addition, this form can know the progress percentage of any buildings constructed. In this report I also told him about space usage female dorm 2. Space usage has a floor area level by level and function of the female dorm 2 building.